Reservoir Sedimentation and Upstream Sediment Sources: Perspectives and Future Research Needs on Streambank and Gully Erosion - Fox, Garey; Sheshukov, Aleksey Y.; Cruse, Rick; Kolar, Randall; Gesch, Karl; Dutnell, Russ (My University, 2016)
The future reliance on water supply and flood control reservoirs across the globe will continue to expand, especially under a variable climate. As the inventory of new potential dam sites is shrinking, construction of additional reservoirs is less likely compared to simultaneous flow and sediment management in existing reservoirs. One aspect of this sediment management is related to the control of upstream sediment sources. However, key research questions remain regarding upstream sediment loading rates. Highlighted in this article are research needs relative to measuring and predicting sediment transport rates and loading due to streambank and gully erosion within a watershed. For example, additional instream sediment transport and reservoir sedimentation rate measurements are needed across a range of watershed conditions, reservoir sizes, and geographical locations. More research is needed to understand the intricate linkage between upland practices and instream response. A need still exists to clarify the benefit of restoration or stabilization of a small reach within a channel system or maturing gully on total watershed sediment load. We need to better understand the intricate interactions between hydrological and erosion processes to improve prediction, location, and timing of streambank erosion and failure and gully formation. Also, improved process-based measurement and prediction techniques are needed that balance data requirements regarding cohesive soil erodibility and stability as compared to simpler topographic indices for gullies or stream classification systems. Such techniques will allow the research community to address the benefit of various conservation and/or stabilization practices at targeted locations within watersheds.
Citation: Fox, G.A., Sheshukov, A., Cruse, R. et al. Environmental Management (2016) 57: 945. doi:10.1007/s00267-016-0671-9
Keywords: Cohesive sediment transport; Gully erosion; Reservoir sedimentation; Streambank erosion